Antioxidant components of Viburnum opulus L. determined by on-line HPLC-UV-ABTS radical scavenging and LC-UV-ESI-MS methods - AYDEMİR, SEZGİN (ELSEVIER SCI LTD, 2015)
Antioxidant activity of the juice and seed and skin extracts prepared with methanol, acetonitrile, and water of Viburnum opulus L. grown in Eastern Black Sea Region were studied with an on-line HPLC-ABTS method and off-line antioxidant methods, among which a linear positive correlation was observed. The fruit extracts were analysed with the HPLC-UV method optimised with 14 standard phenolics. Identification of the phenolic components in the juice was made using an HPLC-UV-ESI-MS method. Nineteen phenolic compounds in juice were identified by comparing the retention times and mass spectra with those of the standards and the phenolics reported in the literature. The major peaks in the juice belonged to coumaroyl-quinic acid, chlorogenic acid, procyanidin B2, and procyanidin trimer. Quite different antioxidant composition profiles were obtained from the extracts with the solvents of different polarities. The antioxidant activities of the seed extracts were higher than those of the skin extracts in general. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Viburnum opulus; Snowball; Gilaburu; On-line HPLC-ABTS/DPPH; FRAP; Polyphenols; PERFORMANCE LIQUID-CHROMATOGRAPHY; MASS-SPECTROMETRY; STRUCTURE ELUCIDATION; DIETARY POLYPHENOLS; ASSAY; IDENTIFICATION; CAPACITY; CATION; QUANTIFICATION; GLYCOSIDES